CLICK: INTERACTIVE APP FOR READING COMPREHENSION - Esgrina, Francisco Jr. Olermo; Generale, Richie Jake Gentapa (LLT Journal: A Journal on Language and Language Teaching, 2023)
For the past decades, technology has been used as a revolutionary aid for education. With recent innovations, it served as a new platform for learning. Since the stirring of the COVID-19 pandemic and the series of global lockdowns, an increase in mobile use has been observed. It solidifies technological innovations grounding as a mode of learning. This study was conducted using the close-group tutorial employing the Accomplish Reading Application as an intervention for remediation among slow learners of primary-grade English. It employed the experimental design where it compared the pre- and post-intervention test results. Indeed, the use of a mobile interactive application is an effective strategy to enhance the comprehension skills of the pupils as observed in their improved and increased test scores.